Aqueous Supercapacitors with Low Cost and High Voltage Enabled by Co‐Solute Crowding Effect of Electrolyte. Issue 22 (17th November 2022) - Wang, Chengshuai; Pu, Yunxun; Feng, Jianze; Xu, Yongtai; Su, Kailimai; Yang, Bingjun; Lang, Junwei; Tian, Guangke
Abstract: Developing high‐voltage and environmentally friendly aqueous electrolytes have become a significant trend in supercapacitors (SCs). However, achieving this goal usually requires the use of "water‐in‐salt" (WIS) electrolytes, inevitably increasing manufacturing costs and sometimes posing problems such as environmental pollution. Here, we developed a water/organic solvent hybrid electrolyte (8 m NaClO4 ‐20 % H2 O‐30 % ACN‐50 % PEG‐200) with low cost and high‐voltage capacity using the water‐miscible polymer polyethylene glycol (PEG) as a crowding agent to suppress water activity, and acetonitrile (ACN) as a co‐solvent to improve the ion transport properties. The synergistic advantages of the two co‐solvents allow SCs using this electrolyte to have a high operative voltage window of up to 2.6 V, currently the highest operating voltage for aqueous carbon‐based SCs, excellent capacity retention (over 11000 cycles) and high energy densities (31.2 Wh kg −1 ). This work provides a promising method for developing green and inexpensive high‐voltage window aqueous electrolytes. Abstract : Higher voltage, lower cost : The electrochemical stability window of the electrolyte is further improved, and good physicochemical properties are maintained by introducing polyethylene glycol and acetonitrile into the "water‐in‐salt" electrolyte. Supercapacitors using this electrolyte can cycle stably and maintain good rate performance at a high operating voltage of 2.6 V with the synergistic advantage of both additives.